Study Implementation of the Minister of Education and Culture's Policy on the Smart Indonesia Program - Prasojo Ashar Nur Darmawan; Agus Sholahuddin; Tommy Hariyanto (Innovation Business Management and Accounting Journal, 2025)
This study aims to describe and analyze the implementation of the Indonesia Smart Card-Lecture (KIP-K) Program at Lumajang University, including identifying and analyzing the factors that support and hinder the program's implementation. The research location was at Lumajang University. The data collection techniques used were observation, interviews, documentation, and Focus Group Discussion (FGD) techniques. Data analysis techniques in this study used qualitative data analysis, collecting all data through interviews, observations, and documentation. The findings in this study show that effective communication, competent human resources, positive disposition, and a solid bureaucratic structure play a key role in ensuring the implementation of the KIP-K Program runs smoothly, according to regulations, and supports student beneficiaries. The program's success is supported by leadership commitment, coordination with LLDIKTI, and the use of SIM KIP-K. However, some obstacles include document collection delays, student absenteeism, field survey limitations, and the threat of cyber attacks. The study results are expected to serve as recommendations for Lumajang University to send regular reminders, record coaching sessions, speed up data verification, strengthen cybersecurity, and form a complaint management team for the smooth running of the KIP-K Program.